Facilitating bricolage through more organic institutional designs? The case of water users' associations in rural Nepal. Issue 2 (September 2016) - Haapala, Juho; Rautanen, Sanna-Leena; White, Pamela; Keskinen, Marko; Varis, Olli
This study scrutinizes the institutional realities of water project implementation in remote, rural Nepal. It demonstrates that both sound institutional design and local bricolage capabilities are required for sustainable operation and maintenance of local institutions in the challenging operational environment. Institutional bricolage processes are best facilitated through providing locally legitimate, inspiring spaces to local agencies for continued learning, adaptation, and innovation. However, the apparent institutional designs do not explicitly facilitate such bricolage processes. We therefore outline more organic institutional design that accounts for and addresses the interlaced institutional design and bricolage processes in development intervention contexts for advancing more sustainable natural resources management.